COVID-19 unemployment and access to statin medications in the United States - Hermosilla, Manuel; Alexander, Caleb; Polsky, Dan (Frontiers in Public Health, 2023)
We investigate whether the unemployment fueled by the spread of the Covid-19 virus in the United States has impacted population access to statin medications. Our empirical strategy relies on comparing statin sales between states where, given the occupational distribution of their workforce, unemployment was more structurally vulnerable to mobility restrictions against states where it was less structurally vulnerable. While we do not find unemployment effects on statin sales on the majority of the population, our estimates link Covid-fueled unemployment with a sharp sales reduction among Medicaid-insured populations, particularly those in working age. For the period between March and August of 2020, these estimates imply a 31% drop of statin sales among this population.